Pengaruh 4P Sepatu Basket Terhadap Minat Beli Generasi Z Di Kota Bandung - William Ruddyanto; Boby Wiryawan Saputra (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study explores how the 4P marketing mix (product, price, place, promotion) impact to the purchase intention of basketball shoes among generation z in Bandung. The growing interest in basketball on Z’s generation makes basketball retails and industries to understand what truly drive their buying decisions. Using quantitative approach and 97 generation z respondents who are living in Bandung. The responses were analysed using multiple linear regression to determine the partial impact and simultaneous impact. The result said product and place do not significantly influence purchase intention in partial way. It means Z’s generation think that product and location is not their main factors. In the other hand, price and promotion got their attention to increase purchase intention. So, Z’s generation are more responsive to price and promotion activity. Although, product and place did not influence individually on purchasing intention, product and place influence simultaneous together with price and promotion on purchasing intention. That mean 4P development still needed because of effect 4P. Overall, the study provides meaningful insight for business to develop their effective marketing strategies for Z’s generation.